Fe3O4–Mn3O4 nanocomposites with moderate magnetism for in vitro cytotoxicity studies on macrophages. Issue 86 (1st September 2016) - Rahaman, Hasimur; Nath, Anupam; Paul, Rimi; Sengupta, Mahuya; Ghosh, Sujit Kumar
Abstract : Reduced magnetism of Fe3 O4 –Mn3 O4 nanocomposites synthesised by alkaline hydrolysis has been explored for in vitro cytotoxicity studies on splenic macrophages. Abstract : Dual magnetic iron oxide/manganese oxide nanocomposites have been synthesised by alkaline hydrolysis of a manganese precursor in the presence of preformed polyethylene glycol (PEG)-stabilised magnetite (Fe3 O4 ) nanoparticles. The formation of the nanocomposites has been characterised by absorption spectroscopy, Fourier transform infrared spectroscopy, transmission electron microscopy, high resolution transmission electron microscopy, dynamic light scattering, selected area electron diffraction patterns, energy dispersive X-ray analysis, elemental mapping, X-ray diffraction patterns, Raman spectroscopy, thermogravimetric analysis and vibrating sample magnetometry. It has been shown that the synthesised Fe3 O4 –Mn3 O4 nanocomposites exhibit reduced magnetism compared to the superparamagnetic Fe3 O4 nanoparticles. The moderate magnetism of the Fe3 O4 –Mn3 O4 nanocomposites offers a viable platform for in vitro cytotoxicity studies on macrophages.